Case Report: Simnotrelvir/Ritonavir are effective in shortening the course of prolonged SARS-CoV-2 infection during anti-CD20 maintenance therapy in patients with follicular lymphoma - Yang, Jing; Tu, Shengke; Peng, Hui; Peng, Yuanyuan; Li, Min; Song, Kui (Frontiers in Oncology, 2025)
Patients with hematologic malignancy had the possibility of persistent infection with COVID-19, particularly those who received anti-CD20 monoclonal antibody therapy for lymphoma, regardless of vaccination status. We report two cases of follicular lymphoma (FL) infected with Omicron virus that could not be confirmed by routine SARS-CoV-2 tests during maintenance therapy with an anti-CD20 agent, obinutuzumab or rituximab. In addition to immunomodulatory drugs, both of them took Simnotrelvir/Ritonavir to effectively alleviate the symptoms. The aim is to highlight the complexity of SARS-CoV-2 infection and to discuss why it is easy to be infected with COVID-19 for a long time in this fragile patient population and the response to such patients with unexplained respiratory symptoms during maintenance therapy. Patients with hematologic malignancies treated with anti-CD20 agent are at considerable risk of a prolonged disease course and recurrence of COVID-19. Specialized prevention, diagnostic and therapeutic strategies should be developed for this group of patients.